Towards standardised and valid anthropometric indicators of nutritional status in middle childhood and adolescence. (October 2022) - Lelijveld, Natasha; Benedict, Rukundo K; Wrottesley, Stephanie V; Bhutta, Zulfiqar A; Borghi, Elaine; Cole, Tim J; Croft, Trevor; Frongillo, Edward A; Hayashi, Chika; Namaste, Sorrel; Sharma, Deepika; Tumilowicz, Alison; et al.
Summary: Recognition of the importance of nutrition during middle childhood (age 5–9 years) and adolescence (age 10–19 years) is increasing, particularly in the context of global food insecurity and rising overweight and obesity rates. Until now, policy makers have been slow to respond to rapidly changing patterns of malnutrition across these age groups. One barrier has been a scarcity of consistent and regular nutrition surveillance systems for these age groups. What should be measured, and how best to operationalise anthropometric indicators that have been the cornerstone of nutrition surveillance in younger children and in adults, has been the topic of ongoing debate. Even with consensus on the importance of a given anthropometric indicator, difficulties arise in interpreting trends over time and between countries owing to the use of different terminologies, reference data, and cutoff points. In this Viewpoint we highlight the need to revisit anthropometric indicators across middle childhood and adolescence, a process that will require WHO and UNICEF coordination, the engagement of national implementors and policy makers, and partnership with research communities and donors.